ANTIOXIDANT ACTIVITIES OF DIFFERENT VARIETIES OF SPENT COFFEE GROUND (SCG) EXTRACTED USING ULTRASONIC-ETHANOL ASSISTED EXTRACTION METHOD - ANSORI, NUR IMAMAH; ZAINOL, MOHD KHAIRI; MOHD ZIN, ZAMZAHAILA (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
Spent coffee grounds (SCG) a by-product from coffee industries, coffee shops and domestic users contain large amounts of organic compounds which could be re-used as source antioxidants for foods or cosmetics. This project aims to study the antioxidant activity of three different spent ground coffee varieties (Robusta, Liberica and Arabica) extracted using ultrasonic-ethanol assisted extraction method utilizing 60% ethanol. The extracted samples were analysed using DPPH, FRAP, FTC and TBA, total phenolic content, total flavonoid content and also individual flavonoids to measure the quality and quantity of antioxidative activity in spent coffee. Robusta and Liberica SCGs exhibited similar activity (p>0.05) towards DPPH scavenging and ferric reducing reaction. Both showed 77.99±0.92 and 77.75±0.04%, respectively for DPPH, and 26.82±2.92 and 24.41±0.49 mg TE/g dry sample, respectively for FRAP. In FTC and TBA analyses, Robusta SCG was found to have the least activity with 61.07±2.43% and 2.9±0.14% respectively. Spent Arabica has similar inhibition percentage (p>0.05) as Liberica SCG in FTC (57.08±0.9 and 50.54±4.23% respectively), yet has different inhibition activity (p<0.05) in TBA (4.3±0.14 and 7.4±1.41% respectively). Total phenolic and flavonoid contents were found to be the highest in Arabica SCG with 941.04±37.25 mg GAE and 78.21 mg QE/g dry sample, respectively. Liberica and Robusta SCGs contain a total of phenolic content of 661.14±2.86 and 547.51±59.5 mg GAE/g dry sample, respectively and a total of flavonoid content of 71.64±1.85 and 20.66±7.82 mg QE/g dry sample. Individual flavonoids of luteolin and quercetin were present in all the three spent ground coffee varieties. Results from the study illustrated that the three different varieties of SCGs showed different extract yields as well as diverse traits of antioxidant activity that could serve as a good antioxidant.